Beyond the numbers: understanding the diversity of covid-19 epidemiology and response in South Asia. (25th June 2021) - Bhutta, Zulfiqar A; Siddiqi, Sameen; Hafeez, Assad; Islam, Muhammad; Nundy, Samiran; Qadri, Firdausi; Sultan, Faisal
Abstract : Zulfiqar A Bhutta and colleagues compare the response in South Asian countries and consider what is needed to contain covid-19 and manage future pandemics